The Social Meaning of Food Consumption Behaviors in Rural Brazil: Agreement and Intracultural Variation. Issue 4 (November 2021) - Weaver, Lesley Jo; Henderson, Nicole; Hadley, Craig
Food insecurity (FI) is often assessed through experienced-based measures, which address the number and extent of coping strategies people employ. Coping indices are limited because, methodologically, they presuppose that people engage coping strategies uniformly. Ethnographic work suggests that subgroups experience FI quite differently, meaning that coping strategies might also vary within a population. Thus, whether people actually agree on FI coping behaviors is an open question. This article describes methods used to test whether there was a culturally agreed on set of coping behaviors around FI in rural Brazilian majority-female heads of household, and to detect patterned subgroup variation in that agreement. We used cultural consensus and residual agreement analyses on freelist and rating exercise data. This process could be applied as a first step in developing experience-based measures of FI sensitive to intragroup variation, or to identify key variables to guide qualitative analyses.